The effect of warming up in the form of a small game on learning outcomes of basketball game passing - Kahan Tony Hendrawan; Novita Nur Synthiawati (PHEDHERAL, 2024)
In learning process of sport subject is started with warming up activity. If the warming up activity is not done, the risk of injury will be bigger. The aim of the warming up is to relax the muscles to work harder. The research aims to know the effect of warming up to the basic technique in basketball game. The method used is quantitative design and the research design uses one group pretest posttest design. The sample is taken by using cluster random sampling. The research population is all of the students of SMA Budi Utomo Jombang with the research sample taken from XI grade with 40 students. Technique of data collection uses research form of referential norm assessment (RNA) with the limit 30 seconds. Passing  is done in the distance of  3 meters from the reflective wall. The result of learning basic technique in passing in basketball game, known that: Tcount bigger than Ttable or 8,22>1,68 in Tcount passing. Then there is effect between the result of test in students’ passing before and after being given warming up in small game. Giving the warming up in game can be as reference for teachers to improve the students’ learning result in passing.